Investigation of piezocone dissipation test interpretation in clay accounting for vertical and horizontal porewater pressure dissipation with a large deformation axisymmetric penetration model - Moug, Diane; Huffman, Andrew; DeJong, Jason T. (Frontiers in Built Environment, 2024)
The piezocone (CPTu) dissipation test is used to characterize how the applied load from the penetrating cone is distributed between the soil and pore fluid during both penetrometer advancement and when penetration is paused. The coefficient of consolidation is often estimated from CPTu dissipation tests by interpreting the rate of excess porewater pressure (∆u) decay to static conditions during a pause in cone penetration. Most CPTu dissipation test interpretation methods are based on Terzaghi consolidation theory for ∆u dissipation at the cone shoulder (u2 position) or cone face (u1 position) and assume that radial ∆u dissipation dominates the response. However, several recent studies show that vertical ∆u migration does contribute to the response. This study uses a large deformation direct axisymmetric cone penetration model to characterize the soil-water mechanical response during CPTu dissipation tests, and in particular, the role of vertical ∆u dissipation on the response at the u1 and u2 positions. Large deformations around the penetrating cone are accommodated with an Arbitrary Lagrangian Eulerian approach. Soil behavior is modeled with the MIT-S1 constitutive model calibrated for Boston blue clay (BBC) soil behavior. ∆u dissipation following undrained cone penetration is simulated with coupled consolidation for BBC with over-consolidation ratios (OCR) of 1, 2, and 4 and a range of hydraulic conductivity anisotropy. The simulated u1 and u2 dissipation responses are presented to study how they are affected by OCR and hydraulic conductivity anisotropy. A correction factor is recommended to account for hydraulic conductivity anisotropy when interpreting the horizontal coefficient of consolidation from CPTu dissipation tests.